(3GdeYRj aj efGbH GdTjN CHj jYRis - (3CMeO Hf CHj GdbGSe Hf eMeO GdReQGfj, CHh GdYHGS GdJGOdj GdUheYj,J (B1013 (3g` s ((3Ydj Hf eMeO Hf eMeO GdOeTbj s)
(3ChdgG (B:s
(3hHYO, deG cGfJ cQGeGJ GdChdjGA heYLRGJ dSjOfG hehdGfG eMeO Udi Gddg Ydjg hSde aef CcQe HgPG GdfUjH SjOfG CHh jYRi abUOJ GdJYQja HHYV s
(3BNQgG (B:s
(3hfSJZaQc Gddge ef RdI GdbOe hGddSGf , CheG WZi Hg Gdbde Gh NWQJ KHJ ai GdLfGf s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B198 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B49s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B680 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B404 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs